A Study of Certain Characteristic Features of Various Printed Documents To Determine The Type Printer Used in Forensic Investigations - et. al., Bhoopesh Kumar Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Printed documents are very frequently encountered in forensic cases as disputed or questioned documents. With increasing number of such cases, the printer inspection in has become a major requirement in questioned document examination in recent years considering the extensive use printers in document creation in comparison to handwritten papers. Also, the counterfeiting of printed documents by various printers have been recorded at a large scale in last two decades. In such cases, it is very much required by the investigators to examine and identify the type of printer used and to establish a linkage of the questioned document with the alleged printer. The current study is focused on the examination, analysis and identification of various types of printed documents on the basis of their specific characteristics including resolution, edge contrast, letter roughness and feathering formed from diverse printers to differentiate and classify them for forensic questioned document examination and to assist the forensic expert and questioned document examiner thorough such investigations. In this study three types of printers i.e. two inkjet printers, two laser printers, and two different dot-matrix printers were used to collected the printed documents. The samples were analyzed using Projectina Inspec-8 and Stereomicroscope. Each printer has its uniqueness in printing documents, and this study aims to figure out that particular uniqueness at the documents after printing from the alleged printer. The observations revealed substantial differences in the letter’s characteristics. This study may be a useful to discriminate the documents printed from different types of printers.